2015
DOI: 10.1536/ihj.14-252
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Diastolic Function Is Impaired at Rest and Worsens With Exercise in Otherwise Healthy Individuals With Insulin Resistance

Abstract: SummaryInsulin resistance (IR) is a pathophysiological condition and is associated with cardiovascular risk factors including heart failure. However, studies demonstrating myocardial abnormalities in the early phases of IR are limited. The aim of this study was to investigate myocardial function in otherwise healthy individuals with IR.Individuals with IR who were free of cardiovascular risk factors and healthy controls were included. Stress echocardiography with tissue Doppler imaging (TDI) was performed. Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…For patients with neither lung diseases nor musculoskeletal diseases, the connection between E/A ratio, systolic blood pressure, diastolic blood pressure, and METS can be explained as the impairment of the exercise capacity caused by diastolic dysfunction and hypertension. This is consistent with previous studies ( 6 , 27 30 ). Notwithstanding, the R 2 , which is used to analyze the explanatory power of the equation, showed that there was a slightly weak correlation between the two sides of the equation.…”
Section: Discussionsupporting
confidence: 94%
“…For patients with neither lung diseases nor musculoskeletal diseases, the connection between E/A ratio, systolic blood pressure, diastolic blood pressure, and METS can be explained as the impairment of the exercise capacity caused by diastolic dysfunction and hypertension. This is consistent with previous studies ( 6 , 27 30 ). Notwithstanding, the R 2 , which is used to analyze the explanatory power of the equation, showed that there was a slightly weak correlation between the two sides of the equation.…”
Section: Discussionsupporting
confidence: 94%
“…In prospective studies, GLS has been shown to be superior to ejection fraction (EF) in predicting mortality in patients with previous CVD or chronic kidney disease (28,29). In terms of diastolic function, e′/a′ ratio is known to be related to stiffness of the left ventricle, and to be impaired in insulin resistance (30) and diabetes (31). Diastolic dysfunction is an entity particularly relevant in patients with diabetes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a significant association of elevated fasting PG and insulin levels with decreased aortic distensibility has been emphasized. 45) Because of the high prevalence of abnormal glucose metabolism in Fontan patients and an adverse impact of insulin resistance on ventricular diastolic function especially during exercise as well as that of postprandial hyperglycemia on endothelial dysfunction, [46][47][48] careful attention to this metabolic issue is needed to anticipate better long-term outcomes in these patients with respect to arterial elasticity.…”
Section: Impaired Glucose Metabolismmentioning
confidence: 99%